CONTEMPORARY BUSINESS: WHEN COMMUNICATION AND CULTURE MEET - Dostanić, Lea (Poslovna ekonomija, 2024)
As cultures in contact are inevitable, we tried to emphasise that the readiness to maintain intercultural communication is essential for survival in a world as globalised as today’s. Due to the inevitable changes that have taken place in the field of modern business, the application of information and communication technologies contributes significantly in areas such as competitive advantages, quality of services and products, and overall corporate activities. In this regard, it is necessary to completely reset attitudes and mentality from the past and change how companies communicate inside and outside their walls with employees, clients, suppliers, and interested parties. As essential for achieving a fruitful outcome, willingness and motivation to understand and get to know the culture with which one cooperates is almost indispensable. To promote a true spirit of collaboration, companies must first recognise communication’s strategic role in their management, implementing a well-defined global communication plan that includes external and internal communication strategies. This approach is vital to establish genuine cooperation between the associates who make up and give life to the organisation. Above all, it is crucial to have a relationship between them and create an effective and efficient communication channel. Therefore, organisations must take an active role in collaboration and knowledge management.